Limiares da cartografia: deambulação, arqueologia e montagem no mapeamento de lugares - Ribeiro, Daniel Melo (2018)
This research deals with communicative and semiotic properties of maps. We investigate alternative mapping practices that encourage new ways of perceiving space, revealing features that are not treated by traditional maps. Considering this motivation, we raise the following question: Which aspects of space could be communicated on a map when the cartographic conventions are questioned? As a corpus, we selected four trends that challenge the cartographic language: map art, locative media, literary cartography, and deep mapping. The selected mapping examples are analyzed through the semiotics of Charles S. Peirce. After this analysis, the research focuses on a trend known as deep mapping, in order to investigate a methodological discussion about mapping places. We propose a model based on three steps: walking, archaeology, and montage. The development of these steps was inspired by the philosophy of Walter Benjamin. We consider that the critique of Modernity developed by Benjamin is linked to the interpretation of urban material culture, whose narrative potential is latent in archaeological fragments. Mapping these fragments begins with a walking exercise, goes through an archaeological reading, and is arranged in a montage procedure. Therefore, the main objective is to propose a model that stimulates the creation of cartographic representations addressing three general properties of deep mapping: the body experience with space (walking), the historical dimension (archaeology) and the critical reading (montage). Based on the arguments developed by Benjamin, we support the hypothesis that the alternative mapping approach underlines the threshold experiences. These experiences are related to the liminal spaces of transition and hybridism, a form of resistance against the cartographic dispositif